Cisplatin otoprotection using transtympanic L‐N‐acetylcysteine: A pilot randomized study in head and neck cancer patients. (1st October 2013) - Yoo, John; Hamilton, Scott J.; Angel, Douglas; Fung, Kevin; Franklin, Jason; Parnes, Lorne S.; Lewis, Denise; Venkatesan, Varagur; Winquist, Eric
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To evaluate the feasibility and efficacy of transtympanic L‐N‐Acetylcysteine (L‐NAC) administration in patients receiving cisplatin chemotherapy for head and neck cancer. Study Design Prospective randomized nonblinded open‐label clinical trial. Methods Transtympanic 2% L‐NAC was administered to one randomly selected ear with the other ear as control in each patient. Primary outcome parameter was the difference in the loss of pure tone averages (PTA) at 2, 4, and 8 kHz between the L‐NAC and control ear at 1 to 2 months following chemotherapy. Results Eleven patients completed the study, with two patients demonstrating significantly better hearing in the L‐NAC treated ear (18.2%). However, for the overall group, the difference in hearing preservation did not reach significance. Two percent L‐NAC administration was well tolerated in this patient population. There were no adverse effects associated with L‐NAC. Conclusion Although the study did not demonstrate a significant benefit overall, transtympanic L‐NAC was associated with significantly better hearing in two patients. Better delivery methods may improve the efficacy of this treatment. L‐NAC remains a promising drug in preventing cisplatin‐induced ototoxicity. Level of Evidence 1b. Laryngoscope, 124:E87–E94, 2014